PENATA RIAS PRIA DI KOTA PEKANBARU - Rahul Roy; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The topic of this research is about makeup men in Pekanbaru City with the formulation of the problem, namely to find out the profile of men who work as makeup artists and find out the reasons behind the reasons men choose jobs as makeup artists. The purpose of this study was to find out the profile of men who worked as makeup artists and to find out the reason they chose as makeup artists. This research is a qualitative descriptive study in collecting research data using purposive sampling technique. The data sources used are primary data sources and secondary data instruments are observation, interviews and documentation. After doing the research, there were 6 makeup informants. The results of research obtained by male makeup artists in Pekanbaru are from different backgrounds, male informants working as makeup artists in Pekanbaru aged 24 to 44 years. 3 informants from the origin area, namely Renggat, Tanjung Balai Karimun and padang. The level of education of 6 informants has 2 bachelor and 1 diploma, the rest are graduated from secondary education. Only 1 informant who worked as a makeup artist as a side job and the other 5 made makeup artists as his permanent job. 2 informants who are widowers or have been married. Working as a makeup artist 6 informants were found to have worked for 4 years to 15 years. The reason that men choose to work as makeup artists is because there are rational actions that make them work have a purpose, namely material and the affectual actions of men who work as makeup artists have a feeling of liking the work without coercion from anyone, the informant said that the makeup artist paid hobby.  Keywords : The Makeup Artist, Works as a Makeup Artist